CD11a regulates hematopoietic stem and progenitor cells - Hou, Lifei; Yuki, Koichi (Frontiers in Immunology, 2023)
Integrin αLβ2 (CD11a/CD18, CD11a) is a critical leukocyte adhesion molecule in leukocyte arrest and immunological synapse formation. However, its role in the bone marrow has not been investigated in depth. Here we showed that CD11a was expressed on all subsets of hematopoietic stem and progenitor cells (HPSCs). CD11a deficiency enhanced HSPCs activity under lipopolysaccharide (LPS) stimulation as demonstrated by a higher HSPC cell count along with an increase in cell proliferation. However, our mixed chimera experiment did not support that this phenotype was driven in a cell-intrinsic manner. Rather we found that the production of IL-27, a major cytokine that drives HSPC proliferation, was significantly upregulated both in vivo and in vitro. This adds a novel role of CD11a biology.